PERANCANGAN PROSES MANUFAKTUR MESIN CETAK INJEKSI PENGOLAH SAMPAH PLASTIK - Michael Prastian Wijaya, (2021)
Plastic garbage is still the second major producer of waste in Indonesia, after organic waste. The amount of plastic garbage generated does not equal the ability of operators or the ease with which it may be processed. "Designing of Manufacturing Process for Plastic Waste Processing Injection Molding Machines" is the topic of this study. which focuses on the process of producing an extruder that can also be utilized as a plastic injection tool. The goal of constructing an extruder machine and a plastic injection machine is for the surrounding community to be able to use plastic waste to make things with a marketable value. Extruders can make filaments for 3D printing, whereas plastic injection tools can make clothes hangers. The cost parameters for each manufacturing process in components, the length of time, and the materials utilized can all be used to create the production process.